Use and Conservation of Medicinal Plants by Indigenous People of Gozamin Wereda, East Gojjam Zone of Amhara Region, Ethiopia: An Ethnobotanical Approach. (19th March 2018) - Amsalu, Nigussie; Bezie, Yilkal; Fentahun, Mulugeta; Alemayehu, Addisu; Amsalu, Gashaw
Abstract : An ethnobotanical study of medicinal plants (MPs) used by the local community has been carried out from January 5, 2014, to February 15, 2015, in Gozamin Wereda of East Gojjam Zone, Ethiopia. The purpose of this study was to identify and document the use and conservation of MPs, along with indigenous knowledge of Gozamin community. Data were collected using semistructured interview, field observation, and focus group discussions. The collected data were assessed quantitatively using fidelity level, Jaccard's Coefficient of Similarity, paired comparisons, direct matrix, and preference rankings. In total 93 MPs distributed under 51 families and 87 genera were identified and for each taxon a local name (Amharic) was documented. Asteraceae with 9 (9.68%) species and Solanaceae with 7 (7.53%) species were families represented by more species in the study area. Out of these MPs collected, 80 plant species were used for the treatment of human ailments, 24 species were used against livestock diseases, and 11 common plant species were listed in both cases. The most frequently used plant parts were the leaves followed by the roots. The major threats to MPs in the study area were agricultural expansion, overgrazing, fire wood collection, mining, and cutting down trees for construction and furniture. Therefore, there is a need for appropriate in situ and ex situ conservation measures.